INDEPENDENT CONTROL STRATEGY for performance improvement of Super Capacitor on MMC DC-DC Converter (International Journal of Food and Nutritional Sciences, 2022)
The vessel integrated power system (IPS) exhibits a rising demand for high-voltage and large-capacity energy storage systems in order to equip additional high-energy pulse loads and enhance power supply reliability. On the basis of this background, this paper focuses on a cascaded DC-DC converter that uses a modular multilevel converter (MMC) and dual active bridges (DAB) to create a super capacitor energy storage system. The abbreviation for the cascaded converter is MMC-DAB. In-depth analyses of the system's topology and modulation scheme are provided in this work. This paper suggests a control method that uses the DAB module of each branch to independently adjust the voltage of the sub-module capacitor while taking into account the drawbacks of the conventional bidirectional power control strategy. The traditional and proposed control's mathematical models